W poszukiwaniu (neo)liberalnych tropów w celach wychowania moralnego wskazanych w podstawie programowej dla I etapu edukacyjnego - Małgorzata Lewartowska-Zychowicz (Problemy Wczesnej Edukacji)
The issue of the article concerns the ideological foundation of the moral education goals formulated in the core curriculum of general education for the first stage of education. The analyzes undertaken are focused on the search for values indicating the presence of liberal and neoliberal moral assumptions in the Regulation of the Minister of National Education of 14 February 2017 on the core curriculum of pre-school education and the core curriculum of general education for primary school.